Identification and characterization of a novel freezing inducible gene, li16, in the wood frog Rana sylvatica - McNally, J Dayre; Wu, Shao-Bo; Sturgeon, Christopher M; Storey, Kenneth B (The FASEB journal, 2002)
The wood frog Rana sylvatica survives for weeks during winter hibernation with up to 65% body water frozen as ice. Natural freeze tolerance includes both seasonal and freeze-induced molecular adaptations that control ice formation, deal with long-term ischemia, regulate cell volume changes, and protect macromolecules. This report identifies and characterizes a novel freeze-inducible gene, li16, that codes for a protein of 115 amino acids. Northern blot analysis showed that li16 transcript levels rose quickly during freezing to reach levels 3.7-fold higher than control values after 24 h; immunoblotting showed a parallel 2.4-fold rise in Li16 protein. Regulatory influences on gene expression were assessed. Nuclear runoff assays confirmed that freezing initiated an increase in the rate of li16 transcription, and analysis of signal transduction pathways via in vitro incubation of liver slices implicated a cGMP-mediated pathway in li16 expression. Gene and protein expression in liver was also strongly stimulated by anoxia exposure, whereas the gene was less responsive to dehydration stress. The strong response of li16 to both freezing and anoxia, and the rapid down-regulation of the gene when oxygen was reintroduced, suggest that the Li16 protein may play a role in ischemia resistance during freezing.